Breast cancer in multiple endocrine neoplasia type 1 (MEN1). (5th May 2021) - Cheah, Seong Keat; Bisambar, Chad Ramese; Pitfield, Deborah; Giger, Olivier; Hoopen, Rogier ten; Martin, Jose-Ezequiel; Clark, Graeme R; Park, Soo-Mi; Parkinson, Craig; Challis, Benjamin G; Casey, Ruth T
Abstract : Summary: A 38-year-old female was identified as carrying a heterozygous pathogenic MEN1 variant (c.1304delG) through predictive genetic testing, following a diagnosis of familial hyperparathyroidism. Routine screening for parathyroid and pituitary disease was negative. However, cross-sectional imaging by CT revealed a 41 mm pancreatic tail mass. Biopsy via endoscopic ultrasound confirmed the lesion to be a well-differentiated (grade 1) pancreatic neuroendocrine tumour (pNET) with MIB1<1%. Biochemically, hyperinsulinaemic hypoglycaemia was confirmed following an overnight fast, which was subsequently managed by diet alone prior to definitive surgery. Pre-operative work-up with octreotide SPECT CT demonstrated avid tracer uptake in the pancreatic lesion and, unexpectedly, a focal area of uptake in the left breast. Further investigation, and subsequent mastectomy, confirmed ductal carcinoma in situ pT2 (23 mm) grade 1, N0 (ER positive; HER2 negative). Following mastectomy, our patient underwent a successful distal pancreatectomy to resect the pNET. Loss of heterozygosity (LOH) at the MEN1 locus was found in both the breast tumour and pNET, thereby in keeping with a 'two-hit' hypothesis of oncogenesis, a suggestive but non-definitive clue for causation. To obtain further support for a causative relationship between MEN1 and breast cancer, we undertook a detailed review of the published literature which overall supports the notion that breast cancer is a MEN1 -related malignancy that presents at a younger age and histologically, is typically of ductal subtype. Currently, clinical guidance regarding breast cancer surveillance in MEN1 does not exist and further research is required to establish a clinical and cost-effective surveillance strategy). Learning points: We describe a case of pNET and breast cancer diagnosed at a young age of 38 years in a patient who is heterozygous for a pathogenic MEN1 variant. Loss of the wild-type allele was seen in both breast tissue and pNET specimen. Breast cancer may be an under-recognised MEN1 -associated malignancy that presents at a younger age than in the general population with a relative risk of 2–3. Further research is required to determine the cost-effectiveness of breast cancer surveillance approach at a younger age in MEN1 patients relative to the general population .